Back pain: An aftermath of Covid‐19 pandemic? A Malta perspective. (6th June 2021) - Grech, Stephan; Borg, Joseph N.; Cuschieri, Sarah
Abstract: Background: Back pain is the commonest musculoskeletal complaint across the world. The Covid‐19 pandemic led to mitigating measures including remote working that enhanced a sedentary lifestyle. The aim of this study was to investigate whether back pain complaints have increased from pre‐Covid‐19 to during the Covid‐19 period among the adult population of Malta, while exploring the possible contributing factors. Methods: An online survey was distributed through social media targeting the adult population of Malta. Questions on sociodemographic data, occurrence of back pain pre‐Covid‐19 and since the onset of Covid‐19 was gathered, along with changes in behavioural attitudes, daily routine and physical activity. Descriptive and multiple logistic regression analyses were performed. Results: Out of the 388 responders, 30% experienced chronic back pain pre‐Covid‐19, 49% experienced back pain since Covid‐19, with the majority of the latter claiming that they never experienced back pain before Covid‐19. Significant changes were present in daily routine and physical activity (PA) patterns. Indeed, continuously sitting down (OR: 15.53; p  ≤ 0.01), no PA (OR: 4.22; p  ≤ <0.01), once a week PA (OR: 5.74; p  ≤ <0.01), two to three times PA a week (OR: 2.58; p  = 0.05) and four to five PA a week (OR: 3.46; p  = 0.02) were associated with experiencing new onset back pain since the onset of Covid‐19, when adjusted for sex, age, education and employment status. Conclusion: The pandemic has changed population behaviour resulting in an enhanced back pain occurrence. This is anticipated to impact the individual's disability adjusted life years as well as increase the burden on the economy and healthcare services. A designated multidisciplinary action plan is recommended to reduce back pain impact.